1985
DOI: 10.1007/bf00607911
|View full text |Cite
|
Sign up to set email alerts
|

The pharmacokinetics and haemodynamics of BTS 49465 and its major metabolite in healthy volunteers

Abstract: The pharmacokinetic and haemodynamic effects of a 200 mg oral dose of BTS 49 465 (7-fluoro-1-methyl-3-methylsulphinyl-4-quinolone) were investigated in a double-blind placebo controlled study. BTS 49 465 was rapidly absorbed and cleared from the systemic circulation with a half-life of 1.6 h by oxidation to the sulphone metabolite. The metabolite was cleared with a half-life of 37.6 h. Saliva concentrations of both BTS 49 465 and its metabolite correlated well with the plasma concentrations. Compared to placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
1

Year Published

1987
1987
1994
1994

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(25 citation statements)
references
References 1 publication
2
22
1
Order By: Relevance
“…The interval between study days was thus 14 days, which is adequate for 95% elimination of the major metabolite of flosequinan (Wynne et al, 1985).…”
Section: Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The interval between study days was thus 14 days, which is adequate for 95% elimination of the major metabolite of flosequinan (Wynne et al, 1985).…”
Section: Designmentioning
confidence: 99%
“…In addition studies in patients with severe congestive heart failure have shown that a single oral dose reduces resting left ventricular filling pressure and systemic vascular resistance (Kessler & Packer, 1987 given to patients in heart failure refractory to diuretics (Elborn et al, 1988). In relation to blood pressure flosequinan produces a fall in both systolic and diastolic pressures in healthy volunteers (Wynne et al, 1985) and patients with untreated moderate essential hypertension (Thien et al, 1987). Further studies are now required to determine its place in the management of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…Flosequinan (7-fluoro-1-methyl-3-methyl-sulphinyl-4-quinolone) is a vasodilator which is active in both veins and arteries [10,11]. It has a hypotensive action [11,12] and, in patients with congestive heart failure, it has been shown to decrease resting preload and afterload while improving cardiac performance [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…It has a hypotensive action [11,12] and, in patients with congestive heart failure, it has been shown to decrease resting preload and afterload while improving cardiac performance [13][14][15]. In patients with congestive heart failure following acute myocardial infarction, the peak haemodynamic effect was observed at 1-2 h post dose [16] with persistent effects over the 4 h post-dose study period.…”
Section: Introductionmentioning
confidence: 99%
“…Yates & Hicks, 1988;Falotico et al, 1989;Greenberg & Touhey, 1990) which may have clinical relevance. Clinical studies have shown that flosequinan has an active sulphone metabolite, BTS 53554, which probably contributes to the overall haemodynamic response in man following oral administration (Wynne et al, 1985).…”
Section: Introductionmentioning
confidence: 99%